The Role of the Deli Serdang District Attorney's Office in Postgraduate Education Management Prosecution of Corruption - Harahap, M. Emirsyah Hussein; Ismaidar, Ismaidar (JURNAL HUKUM SEHASEN, 2025)
The role of the Deli Serdang District Attorney's Office in prosecuting corruption crimes is very important in providing a deterrent effect for perpetrators of corruption. With firm and fair prosecution, the Deli Serdang District Attorney's Office can show that corruption is a serious crime that will not be tolerated. This is expected to create fear and a deterrent effect for other potential perpetrators of corruption, so that they think twice before committing corruption. The deterrent effect is very important to create an anti-corruption culture in society. In addition, it also plays a role in returning state losses due to corruption. Through the prosecution process, the Deli Serdang District Attorney's Office can demand that perpetrators pay compensation or return assets. This study uses empirical legal research through field research. The data collection method used in this study is the library research method and the field research method. Data collection was carried out through interviews conducted at the Deli Serdang District Attorney's Office. The Deli Serdang District Attorney's Office in carrying out prosecution coordinates with other institutions in handling corruption crimes such as Expert Witnesses, the Corruption Eradication Commission (SPDP to avoid overlapping) and the State Detention Center (Detention Center). In addition, it tries to prepare evidence and witnesses in the process of prosecuting corruption crimes by preparing various evidence in court, such as: Coordination with related parties, including the Village Head, Sub-district Head and with witnesses who are directly related to corruption cases in witness examinations at the Investigation stage, an Identity Card (KTP) and Mobile Phone Number are attached.